Peningkatan Self-Care Personal Hygiene Terhadap Risiko Infeksi Saluran Kemih pada Lansia - Kiadzaniko Imanurino; Dinasti Pudang Binoriang (JURNAL ILMIAH KESEHATAN MASYARAKAT DAN SOSIAL, 2026)
Decline in the ability to perform activities of daily living among older adults can lead to poor personal hygiene practices, thereby increasing the risk of infections, including urinary tract infections. This study aims to analyze the effect of improving self-care in personal hygiene on reducing the risk of urinary tract infections in the elderly.The method used was a case study involving a single respondent (Mr. W), with a four-week intervention consisting of one visit per week, each lasting approximately 45 minutes. The intervention included personal hygiene education, practical demonstrations, direct assistance, and environmental modification.The results showed an improvement in both awareness and personal hygiene practices, as indicated by the ability to brush teeth regularly, perform proper genital care after urination, and maintain consistency in changing clothes and underwear, although some habits still required ongoing assistance.In conclusion, a holistic approach through education, assistance, and environmental support is effective in gradually improving personal hygiene practices among older adults. However, continuous efforts are necessary to achieve long-term behavioral consistency.